Existential Crisis: Redefining Ken’s Character in the Barbie Movie - Utami, Arvhi Mega; Nisa, Nadhifa Khoirun (Udayana Journal of Social Sciences and Humanities, 2024)
This paper explores the transformative journey of the character Ken in the live-action adaptation of Barbie (2023), directed by Greta Gerwig. While existing reviews tend to center on Barbie, this paper shifts the spotlight onto Ken, a character often overshadowed by Barbie’s fame. Utilizing a qualitative methodology, the paper employs literature and multiple viewing of the film to gather essential visual information and dialogues related to Ken’s existential crisis. The analytical framework is rooted in existentialism by Soren Kierkegaard and Jean-Paul Sartre, examining key concepts such as existence preceding essence and the importance of subjective experience. This paper aims to provide new insights into Ken’s character, illuminating broader themes of identity, gender roles, and personal development in the movie’s narrative. By analyzing Ken’s existential journey, this paper offers a deeper understanding of individual struggles against societal norms, emphasizing the perspective of marginalized male characters within the film.